Fracture mechanics of pseudoelastic NiTi alloys: review of the research activities carried out at University of Calabria - C. Maletta; F. Furgiuele; E. Sgambitterra (Fracture and Structural Integrity)
This paper reports a brief review of the research activities on fracture mechanics of nickel-titanium based shape memory alloys carried out at University of Calabria. In fact, this class of metallic alloys show an unusual fracture response due to the reversible stress-induced and thermally phase transition mechanisms occurring in the crack tip region as a consequence of the highly localized stresses. The paper illustrates the main results concerning numerical, analytical and experimental research activities carried out by using commercial NiTi based pseudoelastic alloys. Furthermore, the effect of several thermo-mechanical loading conditions on the fracture properties of NiTi alloys are illustrated.